Pengaruh Supervisi Akademik Pengawas Sekolah Dan Motivasi Kerja Guru Terhadap Kompetensi Profesional Guru Matematika Sekolah Menengah Atas Negeri - Daming, Khairiyah (Universitas Negeri Makassar, 2017)
The study aims to discover; (i) the implementation of academic supervision of school supervisor; (ii) teachers’ work motivation, (iii) professional competence of Mathematics teachers of SMAN (Public Senior High School), (iv) the influence of the implementation of academic supervision of school supervisor and teachers, work motivation simultaneously toward professional competence of Mathematics teacher of SMAN, (v) the influence of implementation of academics supervision of school supervisor toward professional competence of Mathematics teachers after considering teachers’ work motivation, (vi) the influence between teachers’ work motivation and professional competence of Mathematics teachers of SMAN after considering the implementation of academic supervision of school supervisor based on teachers’ perception. The study is a survey research. The populations were Mathematics teachers at SMAN in Pinrang and Sidrap District. The samples were obtained by employing Area Proportional Random Sampling. The data was analyzed by using partial correlation and regression. The result of the descriptive analysis indicates that the implementation of academic supervision of school supervisor is in high category, teachers’ work motivation is in high category, and professional competence of Mathematics teachers is in very high category. The results of the research reveal that: (i) academic supervision of school supervisor and teachers’ work motivation simultaneously give influence toward professional competence of Mathematics teacher, (ii) the implementation of academic supervision of school supervisor give influenced towards professional of Mathematics teachers at SMAN after considering Mathematics teachers’ work motivation, (iii) after considering the implementation of academic supervision of school supervisor, there is influence of teachers’ work motivation toward professional competence of Mathematics teachers at SMAN.